PENERAPAN PENDEKATAN INKUIRI BERBASIS KONTEKSTUAL PADA KONSEP HIDROLISIS GARAM DI SMA NEGERI 11 AMBON - Nani Muliyani; Dominggus Tahya (Molluca Journal of Chemistry Education (MJoCE), 2012)
Research had been done to know the increase of student learning result on Salt Hydrolysis Concept with application of inquiry approach based on contextual teaching and learning in Grade XI class SMA Negeri 11 Ambon. This research is quantitative descriptive research, as sample is students in XI IPA1 class. While the post test showed that 29 students (96,67%) are able to reached Complete Criterion Minimum (KKM) already decide by that school. The application of inquiry approach based on contextual teaching and learning can support students’ activities in teaching learning process and made students to think critically and be creative to increase students learning result